THE ROLE OF MILITARY PEDAGOGY IN THE TRAINING OF MILITARY PERSONNEL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the issues of the development of military pedagogy as a means for the future officers' versatile preparation are considered. Modern problems of military pedagogical studies of didactics and education of servicemen. The methodological foundations of the national military pedagogy and its application in the current conditions of the development of military education are specified, and the level of competence of officers in dealing with personnel is touched upon.